src/HOL/HOLCF/Sprod.thy
author wenzelm
Sat, 07 Apr 2012 16:41:59 +0200
changeset 47389 e8552cba702d
parent 45695 b108b3d7c49e
child 49759 ecf1d5d87e5e
permissions -rw-r--r--
explicit checks stable_finished_theory/stable_command allow parallel asynchronous command transactions; tuned;

(*  Title:      HOL/HOLCF/Sprod.thy
    Author:     Franz Regensburger
    Author:     Brian Huffman
*)

header {* The type of strict products *}

theory Sprod
imports Cfun
begin

default_sort pcpo

subsection {* Definition of strict product type *}

definition "sprod = {p::'a \<times> 'b. p = \<bottom> \<or> (fst p \<noteq> \<bottom> \<and> snd p \<noteq> \<bottom>)}"

pcpodef (open) ('a, 'b) sprod (infixr "**" 20) = "sprod :: ('a \<times> 'b) set"
  unfolding sprod_def by simp_all

instance sprod :: ("{chfin,pcpo}", "{chfin,pcpo}") chfin
by (rule typedef_chfin [OF type_definition_sprod below_sprod_def])

type_notation (xsymbols)
  sprod  ("(_ \<otimes>/ _)" [21,20] 20)
type_notation (HTML output)
  sprod  ("(_ \<otimes>/ _)" [21,20] 20)

subsection {* Definitions of constants *}

definition
  sfst :: "('a ** 'b) \<rightarrow> 'a" where
  "sfst = (\<Lambda> p. fst (Rep_sprod p))"

definition
  ssnd :: "('a ** 'b) \<rightarrow> 'b" where
  "ssnd = (\<Lambda> p. snd (Rep_sprod p))"

definition
  spair :: "'a \<rightarrow> 'b \<rightarrow> ('a ** 'b)" where
  "spair = (\<Lambda> a b. Abs_sprod (seq\<cdot>b\<cdot>a, seq\<cdot>a\<cdot>b))"

definition
  ssplit :: "('a \<rightarrow> 'b \<rightarrow> 'c) \<rightarrow> ('a ** 'b) \<rightarrow> 'c" where
  "ssplit = (\<Lambda> f p. seq\<cdot>p\<cdot>(f\<cdot>(sfst\<cdot>p)\<cdot>(ssnd\<cdot>p)))"

syntax
  "_stuple" :: "[logic, args] \<Rightarrow> logic"  ("(1'(:_,/ _:'))")

translations
  "(:x, y, z:)" == "(:x, (:y, z:):)"
  "(:x, y:)"    == "CONST spair\<cdot>x\<cdot>y"

translations
  "\<Lambda>(CONST spair\<cdot>x\<cdot>y). t" == "CONST ssplit\<cdot>(\<Lambda> x y. t)"

subsection {* Case analysis *}

lemma spair_sprod: "(seq\<cdot>b\<cdot>a, seq\<cdot>a\<cdot>b) \<in> sprod"
by (simp add: sprod_def seq_conv_if)

lemma Rep_sprod_spair: "Rep_sprod (:a, b:) = (seq\<cdot>b\<cdot>a, seq\<cdot>a\<cdot>b)"
by (simp add: spair_def cont_Abs_sprod Abs_sprod_inverse spair_sprod)

lemmas Rep_sprod_simps =
  Rep_sprod_inject [symmetric] below_sprod_def
  prod_eq_iff below_prod_def
  Rep_sprod_strict Rep_sprod_spair

lemma sprodE [case_names bottom spair, cases type: sprod]:
  obtains "p = \<bottom>" | x y where "p = (:x, y:)" and "x \<noteq> \<bottom>" and "y \<noteq> \<bottom>"
using Rep_sprod [of p] by (auto simp add: sprod_def Rep_sprod_simps)

lemma sprod_induct [case_names bottom spair, induct type: sprod]:
  "\<lbrakk>P \<bottom>; \<And>x y. \<lbrakk>x \<noteq> \<bottom>; y \<noteq> \<bottom>\<rbrakk> \<Longrightarrow> P (:x, y:)\<rbrakk> \<Longrightarrow> P x"
by (cases x, simp_all)

subsection {* Properties of \emph{spair} *}

lemma spair_strict1 [simp]: "(:\<bottom>, y:) = \<bottom>"
by (simp add: Rep_sprod_simps)

lemma spair_strict2 [simp]: "(:x, \<bottom>:) = \<bottom>"
by (simp add: Rep_sprod_simps)

lemma spair_bottom_iff [simp]: "((:x, y:) = \<bottom>) = (x = \<bottom> \<or> y = \<bottom>)"
by (simp add: Rep_sprod_simps seq_conv_if)

lemma spair_below_iff:
  "((:a, b:) \<sqsubseteq> (:c, d:)) = (a = \<bottom> \<or> b = \<bottom> \<or> (a \<sqsubseteq> c \<and> b \<sqsubseteq> d))"
by (simp add: Rep_sprod_simps seq_conv_if)

lemma spair_eq_iff:
  "((:a, b:) = (:c, d:)) =
    (a = c \<and> b = d \<or> (a = \<bottom> \<or> b = \<bottom>) \<and> (c = \<bottom> \<or> d = \<bottom>))"
by (simp add: Rep_sprod_simps seq_conv_if)

lemma spair_strict: "x = \<bottom> \<or> y = \<bottom> \<Longrightarrow> (:x, y:) = \<bottom>"
by simp

lemma spair_strict_rev: "(:x, y:) \<noteq> \<bottom> \<Longrightarrow> x \<noteq> \<bottom> \<and> y \<noteq> \<bottom>"
by simp

lemma spair_defined: "\<lbrakk>x \<noteq> \<bottom>; y \<noteq> \<bottom>\<rbrakk> \<Longrightarrow> (:x, y:) \<noteq> \<bottom>"
by simp

lemma spair_defined_rev: "(:x, y:) = \<bottom> \<Longrightarrow> x = \<bottom> \<or> y = \<bottom>"
by simp

lemma spair_below:
  "\<lbrakk>x \<noteq> \<bottom>; y \<noteq> \<bottom>\<rbrakk> \<Longrightarrow> (:x, y:) \<sqsubseteq> (:a, b:) = (x \<sqsubseteq> a \<and> y \<sqsubseteq> b)"
by (simp add: spair_below_iff)

lemma spair_eq:
  "\<lbrakk>x \<noteq> \<bottom>; y \<noteq> \<bottom>\<rbrakk> \<Longrightarrow> ((:x, y:) = (:a, b:)) = (x = a \<and> y = b)"
by (simp add: spair_eq_iff)

lemma spair_inject:
  "\<lbrakk>x \<noteq> \<bottom>; y \<noteq> \<bottom>; (:x, y:) = (:a, b:)\<rbrakk> \<Longrightarrow> x = a \<and> y = b"
by (rule spair_eq [THEN iffD1])

lemma inst_sprod_pcpo2: "\<bottom> = (:\<bottom>, \<bottom>:)"
by simp

lemma sprodE2: "(\<And>x y. p = (:x, y:) \<Longrightarrow> Q) \<Longrightarrow> Q"
by (cases p, simp only: inst_sprod_pcpo2, simp)

subsection {* Properties of \emph{sfst} and \emph{ssnd} *}

lemma sfst_strict [simp]: "sfst\<cdot>\<bottom> = \<bottom>"
by (simp add: sfst_def cont_Rep_sprod Rep_sprod_strict)

lemma ssnd_strict [simp]: "ssnd\<cdot>\<bottom> = \<bottom>"
by (simp add: ssnd_def cont_Rep_sprod Rep_sprod_strict)

lemma sfst_spair [simp]: "y \<noteq> \<bottom> \<Longrightarrow> sfst\<cdot>(:x, y:) = x"
by (simp add: sfst_def cont_Rep_sprod Rep_sprod_spair)

lemma ssnd_spair [simp]: "x \<noteq> \<bottom> \<Longrightarrow> ssnd\<cdot>(:x, y:) = y"
by (simp add: ssnd_def cont_Rep_sprod Rep_sprod_spair)

lemma sfst_bottom_iff [simp]: "(sfst\<cdot>p = \<bottom>) = (p = \<bottom>)"
by (cases p, simp_all)

lemma ssnd_bottom_iff [simp]: "(ssnd\<cdot>p = \<bottom>) = (p = \<bottom>)"
by (cases p, simp_all)

lemma sfst_defined: "p \<noteq> \<bottom> \<Longrightarrow> sfst\<cdot>p \<noteq> \<bottom>"
by simp

lemma ssnd_defined: "p \<noteq> \<bottom> \<Longrightarrow> ssnd\<cdot>p \<noteq> \<bottom>"
by simp

lemma spair_sfst_ssnd: "(:sfst\<cdot>p, ssnd\<cdot>p:) = p"
by (cases p, simp_all)

lemma below_sprod: "(x \<sqsubseteq> y) = (sfst\<cdot>x \<sqsubseteq> sfst\<cdot>y \<and> ssnd\<cdot>x \<sqsubseteq> ssnd\<cdot>y)"
by (simp add: Rep_sprod_simps sfst_def ssnd_def cont_Rep_sprod)

lemma eq_sprod: "(x = y) = (sfst\<cdot>x = sfst\<cdot>y \<and> ssnd\<cdot>x = ssnd\<cdot>y)"
by (auto simp add: po_eq_conv below_sprod)

lemma sfst_below_iff: "sfst\<cdot>x \<sqsubseteq> y \<longleftrightarrow> x \<sqsubseteq> (:y, ssnd\<cdot>x:)"
apply (cases "x = \<bottom>", simp, cases "y = \<bottom>", simp)
apply (simp add: below_sprod)
done

lemma ssnd_below_iff: "ssnd\<cdot>x \<sqsubseteq> y \<longleftrightarrow> x \<sqsubseteq> (:sfst\<cdot>x, y:)"
apply (cases "x = \<bottom>", simp, cases "y = \<bottom>", simp)
apply (simp add: below_sprod)
done

subsection {* Compactness *}

lemma compact_sfst: "compact x \<Longrightarrow> compact (sfst\<cdot>x)"
by (rule compactI, simp add: sfst_below_iff)

lemma compact_ssnd: "compact x \<Longrightarrow> compact (ssnd\<cdot>x)"
by (rule compactI, simp add: ssnd_below_iff)

lemma compact_spair: "\<lbrakk>compact x; compact y\<rbrakk> \<Longrightarrow> compact (:x, y:)"
by (rule compact_sprod, simp add: Rep_sprod_spair seq_conv_if)

lemma compact_spair_iff:
  "compact (:x, y:) = (x = \<bottom> \<or> y = \<bottom> \<or> (compact x \<and> compact y))"
apply (safe elim!: compact_spair)
apply (drule compact_sfst, simp)
apply (drule compact_ssnd, simp)
apply simp
apply simp
done

subsection {* Properties of \emph{ssplit} *}

lemma ssplit1 [simp]: "ssplit\<cdot>f\<cdot>\<bottom> = \<bottom>"
by (simp add: ssplit_def)

lemma ssplit2 [simp]: "\<lbrakk>x \<noteq> \<bottom>; y \<noteq> \<bottom>\<rbrakk> \<Longrightarrow> ssplit\<cdot>f\<cdot>(:x, y:) = f\<cdot>x\<cdot>y"
by (simp add: ssplit_def)

lemma ssplit3 [simp]: "ssplit\<cdot>spair\<cdot>z = z"
by (cases z, simp_all)

subsection {* Strict product preserves flatness *}

instance sprod :: (flat, flat) flat
proof
  fix x y :: "'a \<otimes> 'b"
  assume "x \<sqsubseteq> y" thus "x = \<bottom> \<or> x = y"
    apply (induct x, simp)
    apply (induct y, simp)
    apply (simp add: spair_below_iff flat_below_iff)
    done
qed

end